Resident Sleep During Traditional Home Call Compared to Night Float - Chowdhary, Apoorva; Davis, John A.; Ding, Leona; Taravati, Parisa; Feng, Shu (Journal of Academic Ophthalmology, 2023)
Purpose This article aims to compare resident sleep while on night float with a traditional home call.Methods We conducted a crossover observational study assessing sleep patterns of seven postgraduate year-2 ophthalmology residents at the University of Washington from 2019 to 2021 using the Fitbit Alta HR device. Overnight call was scheduled from 5 p.m. to 8 a.m. on weekdays, and 8 a.m. to 8 a.m. on weekends. The residency program implemented a partial night float rotation, during which two to three nights of consecutive call were assigned to a resident without other clinical duties. Sleep was recorded using the Fitbit Alta HR for residents while on a 5-week partial night float rotation, on 10-week home call rotations, with postcall relief, and for stretches of seven or more days without call responsibilities. Mixed model regression analysis was used to compare average sleep on home call, night float, and periods without call.Results Sleep data were recorded for a total of 1,015 nights, including 503 nights on home call rotation and 230 nights on night float rotation. Residents slept more during periods away from call compared to either night float or home call rotations (p < 0.001). Residents experienced increased average overall sleep during 10-week rotations on night float compared to home call (p = 0.008). While there was no difference in overnight sleep on call between night float and home call (p = 0.701), residents experienced more sleep overall while on call on night float compared to home call due to more sleep being recorded during postcall naps (p = 0.016).Conclusion Implementing a night float system can increase resident sleep by allowing for more sleep recovery during time away from clinical duties.
Keywords: call; night float; home call; ophthalmology residency; postcall relief; resident sleep